2014
DOI: 10.1007/s11999-013-3349-0
|View full text |Cite
|
Sign up to set email alerts
|

High-energy Femur Fractures Increase Morbidity but not Mortality in Elderly Patients

Abstract: Background Trauma centers are projected to have an increase in the number of elderly patients with high-energy femur fractures. Greater morbidity and mortality have been observed in these patients. Further clarification regarding the impact of high-energy femur fractures is necessary in this population. Questions/purposes Our purpose was to assess the influence of high-energy femur fractures on mortality and morbidity in patients 60 years and older. Specifically, we asked (1) if the presence of a high-energy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…Moreover, histological findings of incomplete atypical fractures show a thin fracture line with signs of attempted but impaired healing typical of insufficiency or fatigue fractures . However, the theory of different fracture mechanisms as an underlying explanation for our observed differences in mortality rates when we compare atypical fractures with ordinary fractures is contradicted by the observation that even higher energy load differences do not seem to influence mortality rates after femoral fractures in the elderly …”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Moreover, histological findings of incomplete atypical fractures show a thin fracture line with signs of attempted but impaired healing typical of insufficiency or fatigue fractures . However, the theory of different fracture mechanisms as an underlying explanation for our observed differences in mortality rates when we compare atypical fractures with ordinary fractures is contradicted by the observation that even higher energy load differences do not seem to influence mortality rates after femoral fractures in the elderly …”
Section: Discussioncontrasting
confidence: 56%
“…(13) However, the theory of different fracture mechanisms as an underlying explanation for our observed differences in mortality rates when we compare atypical fractures with ordinary fractures is contradicted by the observation that even higher energy load differences do not seem to influence mortality rates after femoral fractures in the elderly. (42) The hypothesis of a difference in traumatic impact has another important weakness in that atypical fractures are to a large extent "ordinary" fractures: the femur is weakened by the fatigue crack on the lateral aspect of the shaft, (6,43) but then breaks just like any other fracture (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be attributed to both patient demographics as well as data collection methodology. These findings are supported by Patel et al who demonstrated among the elderly patient population, the mechanism of injury was associated with higher morbidity, longer hospital LOS, increased complication rate, as well as concomitant long bone fractures[14].Although hip fracture patients reported higher absolute rates of comorbidities compared to DF fracture patients, specific risk factors differences reached statistical significance among the DF fracture patients including: alcoholism, CVA, COPD, chronic renal failure, congestive heart failure, tobacco use, cancer with current chemotherapy, and dementia. Moloney et.al.…”
supporting
confidence: 68%
“…Patel and other workers obtained 21% mortality at 1 year of follow up in his series (Patel et al, 2014). This patient died from complications of a co-morbid condition (advanced prostatic cancer).…”
Section: Discussionmentioning
confidence: 83%